2017
DOI: 10.1186/s12940-017-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

Variability and predictors of urinary concentrations of organophosphate flame retardant metabolites among pregnant women in Rhode Island

Abstract: BackgroundOrganophospate flame retardants (PFRs) are chemicals of emerging concern due to restrictions on polybrominated diphenyl ether flame retardant formulations. We describe the occurrence, variability, and predictors of urinary metabolites of PFRs among pregnant women.MethodsIn 2014–2015, 59 women from Providence, RI provided up to 3 spot urine samples during pregnancy (~12, 28, and 35 weeks’ gestation). We created a pooled urine sample per woman and measured nine relevant metabolites in individual and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
66
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 43 publications
15
66
4
Order By: Relevance
“…In almost all available studies, di-ortho-cresyl phosphate (DoCP) and/or di-para-cresyl phosphate (DpCP) (determined alone or together) were detected only occasionally, and/or at relatively low levels (i.e. median levels <0.02 µg/l) in recent studies in China and USA, suggesting limited exposure to the precursors of these metabolites in these general populations (Schindler et al, 2013;Fromme et al, 2014;Kosarac et al, 2016;Lu et al, 2017;Romano et al, 2017;Chen et al, 2018;Ospina et al, 2018). However, higher frequencies were reported in some occupationally exposed populations (Jayatilaka et al, 2017, Tao et al, 2018.…”
Section: General Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In almost all available studies, di-ortho-cresyl phosphate (DoCP) and/or di-para-cresyl phosphate (DpCP) (determined alone or together) were detected only occasionally, and/or at relatively low levels (i.e. median levels <0.02 µg/l) in recent studies in China and USA, suggesting limited exposure to the precursors of these metabolites in these general populations (Schindler et al, 2013;Fromme et al, 2014;Kosarac et al, 2016;Lu et al, 2017;Romano et al, 2017;Chen et al, 2018;Ospina et al, 2018). However, higher frequencies were reported in some occupationally exposed populations (Jayatilaka et al, 2017, Tao et al, 2018.…”
Section: General Populationmentioning
confidence: 99%
“…Tert-butyl phenyl phenyl phosphate (tb-PPP) and bis(2-ethylhexyl) phosphate (BEHP) were detected infrequently (Su et al, 2015;Butt et al, 2016;Castorina et al, 2017b;Hoffman et al, 2017a;Soubri et al, 2017;Carignan et al, 2018a and b;Deziel et al, 2018;He et al, 2018a;Hoffman et al, 2018;Ingle et al, 2018;Sun et al, 2018). Dibenzyl phosphate (DBzP) was not detected in urine samples collected in the U.S.A. (Romano et al, 2017;Jayatilaka et al, 2017;Ospina et al, 2018).…”
Section: General Populationmentioning
confidence: 99%
“…One way to address the issues related to exposure misclassification of nonpersistent compounds is to pool multiple urine samples collected from individuals, as originally recommended by Perrier et al and practiced by others [ 13 ]. This is a cost-effective solution, as it negates the need to conduct assays on dozens of urine samples and then take the average; instead, the pooled sample provides the arithmetic average of those samples while only requiring a single assay to be conducted per participant.…”
Section: Estimating Exposure To Environmental Chemicalsmentioning
confidence: 99%
“…We also identified mechanistic evidence pointing towards an effect of TPhP and TBBPA on metabolic disorders but only very few studies addressed these adverse effects in animal models or in humans. For example, several in vitro studies reported adipogenesis and/or lipid accumulation and two studies showed increase in body weight associated with TPhP exposure in humans and rodents, and with TBBPA exposure in fish [6,35,52,55,56,65,66,70]. In addition, activation of PPARγ (the MIE of AOP 72 that leads to obesity) by TPhP and TBBPA has been reported in many in vitro studies, two ToxCast assays and in zebrafish, with effective doses below 1 µM for TBBPA only (for example: [17,54,55]).…”
Section: Possible Aos Of Cat I Frs Predicted From Aop Searchmentioning
confidence: 99%